Comparing group-based acceptance and commitment therapy (ACT) with enhanced usual care for adolescents with functional somatic syndromes: a study protocol for a randomised trial. Issue 9 (15th September 2016) - Kallesøe, Karen Hansen; Schröder, Andreas; Wicksell, Rikard K; Fink, Per; Ørnbøl, Eva; Rask, Charlotte Ulrikka
Abstract : Introduction: Functional somatic syndromes (FSS) are common in adolescents, characterised by severe disability and reduced quality of life. Behavioural treatments such as acceptance and commitment therapy (ACT) has shown promising results in children and adolescents with FSS, but has focused on specific syndromes such as functional pain. The current study will compare the efficacy of group-based ACT with that of enhanced usual care (EUC) in adolescents with a range of FSS operationalised by the unifying construct of multiorgan bodily distress syndrome (BDS). Methods and analysis: A total of 120 adolescents aged 15–19 and diagnosed with multiorgan BDS, of at least 12 months duration, will be assessed and randomised to either: (1) EUC: a manualised consultation with a child and adolescent psychiatrist and individualised treatment plan or (2) manualised ACT-based group therapy plus EUC. The ACT programme consists of 9 modules (ie, 27 hours) and 1 follow-up meeting (3 hours). The primary outcome is physical health, assessed by an Short Form Health Survey (SF-36) aggregate score 12 months after randomisation. Secondary outcomes include self-reported symptom severity, symptom interference, depression and anxiety, illness worry, perceived stress and global improvement; as well as objective physical activity and bodily stress response measured by heart rate variability, hair cortisol and inflammatory biomarkers. Process measures are illness perception, illness-related behaviour and psychological flexibility. Ethics and dissemination: The study is conducted in accordance with Helsinki Declaration II. Approval has been obtained from the Science Ethics Committee of the Central Denmark Region and the Danish Data Protection. The results will be sought to be published according to the CONSORT statement in peer-reviewed journals. Discussion: This is one of the first larger randomised clinical trials evaluating the effect of a group-based intervention for adolescents with a range of severe FSS. Trial registration number: NCT02346071 ; Pre-results.